A study on sexual violence among women in Northern Ethiopia's 2022 conflict: mixed methods - Kidie, Atitegeb Abera; Masresha, Seteamlak Adane; Ayal, Birtukan Gizachew; Mekuria, Kindie; Kodo, Tsion Kokeb; Boye, Abayneh Tunta; Tiruneh, Misganaw Guadie; Bizuneh, Fassikaw Kebede; Fenta, Eneyew Talie (Frontiers in Global Women's Health, 2025)
BackgroundViolence against women is both a human rights violation and a significant reproductive health issue, causing substantial morbidity. It's a pervasive global public health concern, particularly prevalent in developing regions like sub-Saharan Africa. Ethiopia faces this issue extensively despite its preventable nature, persisting as a significant challenge within the country.ObjectiveThe study aimed to identify the extent and factors associated with sexual violence among women, children, and adolescent girls during the 2022 armed conflict in Northern Ethiopia.MethodA community-based cross-sectional study combined quantitative and phenomenological methods. We used multistage and snowball sampling, involving 574 individuals along with 10 in-depth interviews and 3 focus group discussions (FGDs). Statistical analysis relied on Stata version 16 and open code version 4.03. Quantitative analysis employed multivariable binary logistic regression, while qualitative data underwent thematic analysis.ResultThe study found a 9.76% prevalence of sexual violence, with 2.4% experiencing rape during the conflict. Prostitutes faced a fourfold increased risk (AOR: 4.2, 95% CI: 1.3, 10.9). Living in areas with attacks raised the risk 2.7 times (AOR: 2.7, 95% CI: 1.1, 6.2), and a monthly income of 2,001–4,000 ETB increased it 2.5 times (AOR: 2.5, 95% CI: 1.1, 5.7). The impacts included psychosocial effects, stigma, and fear of humiliation, divorce, and displacement.ConclusionApproximately one in ten women experienced sexual violence during the conflict. Factors such as being a prostitute, having a lower income, and living in attacked villages were significant predictors of this violence. The main impacts included psychosocial effects, external blame, and stigma, fear of humiliation, divorce, and displacement.